Evaluation of Five Different Models of Valiantzas Method in Estimating Reference Crop Evapotranspiration (Case Study: Lorestan Province) - Khashayar Peyghan; Shakoor Tafi; Zahra Miri; Amir Soltani; Milad Pour Mansouri (Nīvār)
Reference crop evapotranspiration and its accurate estimation play an essential role in irrigation planning, irrigation interval determination and in studies related to water balance modeling in each region. Valiantzas method is one of the newest methods for calculating reference evapotranspiration, the advantages of which include simple application in regional calibration and hydrological applications. In this study, in order to evaluate the accuracy of five different models of Valiantzas method, monthly reference evapotranspiration during the years 1999 to 2018, in nine meteorological stations of Lorestan province (Azna, Aleshtar, Aligudarz, Boroujerd, Poldakhtar, Khorramabad, Dorod, Kuhdasht, Noorabad) were calculated and the results were compared with the FAO-56 reference method. The results showed that based on RMSE and CRM statistics, Valiantzas 2 model and based on R2 statistics, Valiantzas 4 model recorded the best performance in estimating reference evapotranspiration. By station as well, the Valiantzas 4 model in five stations and the Valiantzas 2 model in four stations provided the most accurate performance, and as a result, the Valiantzas 4 and 2 models can be suggested for use in Lorestan province. In addition, in four stations the Valiantzas 5 model, in four stations the Valiantzas 3 model and in one station the Valiantzas 1 model by the weakest performance, indicated that they are not suitable for use in Lorestan province. In general, despite the under estimation in the reference evapotranspiration calculation, all five models of Valiantzas method had an acceptable closeness with FAO-56 method and the results of this method can be considered reliable.